PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNINGDAN MODEL PEMBELAJARAN KONVENSIONAL TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARANMATEMATIKA DI KELAS V SDN 068003 P.SIMALINGKAR MEDAN TAHUN PEMBELAJARAN 2018/2019 - SITUMORANG, VALEN ANASTASYA (Jurnal Ilmiah Aquinas, 2019)
This study aims to determine the effect of using Problem Based Learning models on students’ learning outcomes. This research was conducted at SDN 068003 P.Simalingkar Medan in July 2018. The subjects of research were 33 students’. The research method is a One Shot Case Study that is carried out in one class. The instrument used to collecting the data is a multiple choice test. Hypothesis testing is done using the "t-test".The results of statistical calculations showed that the students' mathematics learning outcomes using conventional learning models included in the sufficient category with the students’ mean score is 64.24, while the learning outcomes through the Problem Based Learning model in the excellent category with the mean score is 80.90. Furthermore, hypothesis testing shows that t count is 83.3 and then consulted with table t at the significant α = 0.05 with dk = 64 is 1.67. Therefore, the tcount obtained is greater than t table that is 83.3> 1.67 so it is proven that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. So it can be concluded that the Problem Based Learning model influences for the students’ learning outcomes in Mathematics subjects at the fifth grade students’ of SDN 068003 P.Simalingkar Medan in academic year 2018/2019. Thus, this learning model is appropriate for use in the learning process.